2020
DOI: 10.1093/ijpp/riaa015
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy students’ attitude towards providing pharmaceutical care to patients with anxiety and their knowledge of psychotropic medicines in Jordan

Abstract: Objectives To describe pharmacy students’ attitude towards providing pharmaceutical care (PC) to patients with anxiety and their knowledge of psychotropic medicines (PM). Methods A cross-sectional emailed survey was sent to all 200 pharmacy students (fourth and fifth year) in one Jordanian university. Statistical analysis included descriptive statistics and chi-square test. Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…The majority of the studies employed a cross‐sectional survey‐based methodology ( n = 8), 28,29,31–36 while one study used a mixed‐methods study design, with a quantitative phase and a qualitative phase 30…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of the studies employed a cross‐sectional survey‐based methodology ( n = 8), 28,29,31–36 while one study used a mixed‐methods study design, with a quantitative phase and a qualitative phase 30…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 provides a summary of the descriptive characteristics of the studies included in the review. The included studies were reported from Jordan ( n = 4), 29,30,34,36 Kuwait ( n = 2), 31,33 Qatar ( n = 2), 31,32 Saudi Arabia ( n = 1), 28 and United Arab Emirates ( n = 1) 35 . The target populations in all the studies were BSc pharmacy students, 28–36 and PharmD degree 34–36 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations